STRATEGI PEMBIAYAAN THEORY OF CONSTRAINTS: PENUNTASAN FONDASI CALISTUNG JENJANG SMP NEGERI DI KALIMANTAN TIMUR - Indri; Widyatmike Gede Mulawarman; Mukhamad Nurhadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Introduction: The incomplete foundation of reading, writing, and arithmetic (reading, writing, and arithmetic) in public junior high schools in East Kalimantan is crucial for school management to develop strategies to address this issue, while maintaining budget efficiency. The purpose of this research is to use the TOC approach as a solution. Method: The research employed a phenomenological approach, a systematic literature review procedure, and relevant keywords. Results: The research indicates that the incomplete foundation of reading, writing, and arithmetic can be addressed through the use of the TOC strategy. Discussion: The TOC stages of the education financing strategy are: identify, exploit, subordinate, elevate, and repeat. Currently, the foundation of reading, writing, and arithmetic is crucial, as previous studies have shown.